Ruang Lingkup Perlindungan Hak Kekayaan Intelektual Terhadap Video Game - Ramadhan, Galih Dwi (JIPRO: Journal of Intellectual Property, 2021)
Intellectual Property Rights exist to protect the intellectual property rights of a human being. A video game which is an entertainment that is played digitally is one of the results of human intellectual work. Video games are a very complex human intellectual work because various other intellectual works are combined into a video game. Due to the complexity of a video game as a human intellectual work, there must be certainty of the scope of intellectual property rights protection that can be used to protect video games as human intellectual works. Juridical normative studies are used to examine the scope of intellectual property rights protection for a video game. Copyright and industrial property rights can be applied and used to protect video games.